Understanding the relationship between dog ownership and children's physical activity and sedentary behaviour. Issue 5 (13th December 2012) - Christian, H.; Trapp, G.; Lauritsen, C.; Wright, K.; Giles‐Corti, B.
Summary: What is already known about this subject: Dog ownership is a catalyst for physical activity in adults. Approximately 50–70% of Australian households with children have a dog. Dog‐facilitated physical activity may be an effective way to increase physical activity and decrease child overweight and obesity. What this study adds: Dog ownership was associated with self‐reported walking and physical activity, but not parent‐report screen use or measured weight status. The results highlight the potential for dog ownership to significantly impact children's physical activity levels. Within dog‐owning families, the promotion of walking and active play with a dog may be a strategy to increase children's physical activity and curb obesity. Background: Dog ownership is a catalyst for physical activity in adults. Given 50–70% of Australian households with children have a dog, dog‐facilitated physical activity may be an effective way to increase physical activity and decrease child obesity. Objective: We hypothesized that children with a family dog walk more, are more physically active and are more likely to achieve recommended levels of weekly physical activity compared with children who do not have a dog. Method: Cross‐sectional data from the Western Australian TRravel, Environment, and Kids project (TREK) were analyzed for 1218 children aged 10–12 years. Individual and environment factors, child physical activity, walking, screen use, sedentary behaviour and dog ownership status was collected from child and parent questionnaires. Children's height and weight were measured. Results: Approximately 60% of children had a family dog. Dog ownership was associated with, on average, 29 more minutes of walking and 142 more minutes of physical activity per week ( P ≤ 0.01). After adjustment, children with a dog were 49% more likely to achieve the recommended level of weekly physical activity (420 min) and 32% more likely to have walked in their neighbourhood in the last week, compared with non‐dog owners ( P ≤ 0.05). These relationships varied by gender. Dog ownership was not associated with screen use or weight status. Conclusions: Dog ownership was associated with walking and physical activity, but not screen use or weight status. Within dog‐owning families, the promotion of walking and active play with a dog may be a strategy to increase children's physical activity.